Validated Mean Centering Ratio UV Spectrophotometric Method for the Determination of Bromhexine Hydrochloride and Guaifenesin in Syrup Dosage Form - Tarigan Rida Evalina; Muhammad Azzam; Mayang Sari; Gadhave, Ankita; Lilik Septiana (Asian Journal of Pharmaceutical Research and Development, 2026)
Bromhexine hydrochloride and guaifenesin are frequently combined in syrup formulations; however, their zero-order UV absorption spectra exhibit considerable overlap, which limits direct spectrophotometric analysis. This study aimed to develop and validate a simple and selective mean centering of ratio spectra (MCR) method for the simultaneous determination of bromhexine hydrochloride and guaifenesin in syrup dosage form. Zero-order absorption spectra were recorded over the wavelength range of 200–400 nm, and the overlapping spectra were resolved using ratio spectra followed by mean centering. The method exhibited linear responses over concentration ranges of 54–74 µg/mL for bromhexine hydrochloride and 74–94 µg/mL for guaifenesin. Method validation was performed in accordance with International Council for Harmonisation (ICH) guidelines. Accuracy, evaluated using the standard addition method at three concentration levels (80%, 100%, and 120%), showed satisfactory recoveries, while precision studies demonstrated low relative standard deviation values. The obtained limits of detection and quantification confirmed adequate method sensitivity. The proposed MCR method is simple, accurate, precise, and cost-effective, making it suitable for routine quality control analysis of bromhexine hydrochloride and guaifenesin in combined syrup formulations.